2021
DOI: 10.1021/acsapm.1c01254
|View full text |Cite
|
Sign up to set email alerts
|

Control of Drug Release from Microparticles by Tuning Their Crystalline Textures: A Structure–Activity Study

Abstract: Predicting drug release profiles from polymer microparticles has proven challenging due to the numerous environmental and chemical factors that affect the device and influence the rate of drug release. By measuring the various polymer properties that can influence drug release, a predictive approach can be used to select polymers with specific properties that will lead to the desired release profile for the application. To illustrate this, a library of tyrosol-derived poly(ester-arylate)s, poly(amide)s, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…11,12 Importantly, the remarkable advantages in blood–brain barrier crossing nanotechnology make brain tumor imaging and therapy a great opportunity. 11,14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Importantly, the remarkable advantages in blood–brain barrier crossing nanotechnology make brain tumor imaging and therapy a great opportunity. 11,14…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Importantly, the remarkable advantages in blood-brain barrier crossing nanotechnology make brain tumor imaging and therapy a great opportunity. 11,14 Brain tumors are life-threatening diseases, bearing a low survival rate for patients. 15,16 According to the World Health Organization (WHO) classification in the year 2021 (Fig.…”
mentioning
confidence: 99%
“…Alternatively, we propose that latency in FROMP resins can be achieved via a localized separation between monomer and active catalyst that can be removed upon exposure to an external stimulusa technique ubiquitous in biological systems. , An established way to delay contact between reactive pairs is the encapsulation of molecular cargo in the form of polymer microparticles (PMPs). This well-studied method has been applied to the controlled release of drug molecules, , catalyst species, and polymerization initiators. Pojman et al demonstrated that microencapsulation of organic peroxide initiators increases the storage life of free-radical acrylate FP . Extended storage times (>1 day) resulted in significant decreases in the mechanical properties of the polymer products and SP still occurred within a two month period.…”
Section: Introductionmentioning
confidence: 99%